Gemin proteins are required for efficient assembly of Sm-class ribonucleoproteins - Shpargel, Karl B. (National Academy of Sciences, 2005)
Spinal muscular atrophy (SMA) is a neurodegenerative disease characterized by loss of spinal motor neurons. The gene encoding the survival of motor neurons (SMN) protein is mutated in >95% of SMA cases. SMN is the central component of a large oligomeric complex, including Gemins2–7, that is necessary and sufficient for the in vivo assembly of Sm proteins onto the small nuclear (sn)RNAs that mediate pre-mRNA splicing. After cytoplasmic assembly of the Sm core, both SMN and splicing snRNPs are imported into the nucleus, accumulating in Cajal bodies for additional snRNA maturation steps before targeting to splicing factor compartments known as “speckles.” In this study, we analyzed the function of individual SMN complex members by RNA interference (RNAi). RNAi-mediated knockdown of SMN, Gemin2, Gemin3, and Gemin4 each disrupted Sm core assembly, whereas knockdown of Gemin5 and Snurportin1 had no effect. Assembly activity was rescued by expression of a GFP-SMN construct that is refractive to RNAi but not by similar constructs that contain SMA patient-derived mutations. Our results also demonstrate that Cajal body homeostasis requires SMN and ongoing snRNP biogenesis. Perturbation of SMN function results in disassembly of Cajal bodies and relocalization of the marker protein, coilin, to nucleoli. Moreover, in SMN-deficient cells, newly synthesized SmB proteins fail to associate with U2 snRNA or accumulate in Cajal bodies. Collectively, our results identify a previously uncharacterized function for Gemin3 and Gemin4 in Sm core assembly and correlate the activity of this pathway with SMA.